Morbidity after percutaneous liver biopsy. Issue 9 (September 1987) - Lichtman, S; Guzman, C; Moore, D; Weber, J L; Roberts, E A
Abstract : The safety of percutaneous liver biopsy with a 1.2 mm Menghini needle in infants aged one year or less was investigated. One hundred and eighty four procedures performed from 1975 to 1985 were reviewed. There were no deaths or major complications within 48 hours associated with the procedure. In five instances specific complications occurred: a drop in haemoglobin concentration (three), transient hypotension (one), and haematoma at the biopsy site (one). The result of liver biopsy was diagnostic in 83% of cases, compatible with unspecified metabolic disease in 8%, and normal or not diagnostic in 9%. This study suggests that percutaneous liver biopsy can be performed with relative safety in small infants if coagulation is normal and there are no major contraindications, and the results yield important diagnostic information which cannot be obtained using less invasive procedures.